Problem wykorzystania ziemi w Polsce w warunkach rolnictwa zrównoważonego - Urban, Stanisław (Issue of land utilizing in Poland from the aspect of sustainable agriculture, 2007)
Poland has sufficient resources of agricultural land, where there is 0,5 ha of utilized land per one person. However, sińce rapid drop of arabie land and forests is dangerous, these resources should be protected. The work describes methods of the land protection. It is stated that the land protection is the basis of the sustainable agriculture rules and creates favourable conditions for restoring biological balance in the soil environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 325-333